2012
DOI: 10.1111/j.1750-3841.2012.02782.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Very Low Levels of 5‐(Hydroxymethyl)‐2‐furaldehyde (HMF) in Natural Honey: Comparison Between the HPLC Technique and the Spectrophotometric White Method

Abstract: This work can help governmental and private laboratories that perform food analyses to choose the best method for the determination of HMF at very low levels in unifloral honey and honeydew samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…where Sa = standard deviation of the intercept of regression line and b = slope of the calibration curve [53,54]. The LOD in air was calculated by the formula: LOD in air (ng·m −3 ) = concentrations in solution (µg·L −1 ) × 0.045 L/72 m −3 .…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 99%
“…where Sa = standard deviation of the intercept of regression line and b = slope of the calibration curve [53,54]. The LOD in air was calculated by the formula: LOD in air (ng·m −3 ) = concentrations in solution (µg·L −1 ) × 0.045 L/72 m −3 .…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 99%
“…9 HPLC has a better reproducibility and repeatability than the Winkler method and is marginally better than the White method. 4,6 This is supported by the fact that the IHC 9 highlighted that differences between HPLC and the spectrophotometric results are more apparent at lower concentrations. Truzzi et al 4 suggested avoiding using HPLC for HMF concentrations below 1 mg kg À1 .…”
Section: Hplc Methodsmentioning
confidence: 82%
“…5 This method produces the smallest percentage relative standard deviation of reproducibility (RSD R ) range of 6.1-10.9% out of all recommended methods. Truzzi et al 4 suggested avoiding using HPLC for HMF concentrations below 1 mg kg À1 . 3 For 23 out of 25 FAPAS Series 28 PTs, participants mainly used HPLC for HMF analysis compared to a spectrophotometric method.…”
Section: Hplc Methodsmentioning
confidence: 99%
“…Thus it is thought that HMF may have toxic effects (carcinogenic, mutagenic, genotoxic and cytotoxic) producing human health risks. So it becomes essential to carry out studies on the distribution of this contaminant in foods (Capuano & Fogliano, 2011;Truzzi, Annibaldi, Illuminati, Finale, Rossetti, & Scarponi, 2012). Despite of the economic importance of cane and corn syrups, it is emphasized that we could not find any earlier study about the HMF distribution in these foods produced in Brazil.…”
Section: Introductionmentioning
confidence: 97%
“…The analytical methodology more usually adopted is the liquid chromatography with ultraviolet detection (HPLC-UV) due to characteristics such as cost, resolution, versatility and sensitivity (Gaspar & Lucena, 2009;Lemos, Santos, & Santos, 2010;Spano et al, 2006;Ameur et al, 2006;Gökmen & Senyuva 2006;Capuano & Fogliano, 2011;Truzzi et al, 2012;Zhang, Wei, Liu, Lin, & Yuan, 2013).…”
Section: Introductionmentioning
confidence: 99%